Welcome, recorder, to the full-time school! - Santa Cruz, Jevison (Revista do Colóquio, 2024)
This work aims to present how sixth-grade students from a full-time school located in the north area of Recife-PE, were inserted into the universe of music in an elective subject through the use of the recorder. The methodology used was qualitative, focusing on descriptive elements, bibliographic research, and in a systematic and participatory observation. Regarding lesson planning, it was organized weekly. As a result, it was observed that the students acquired knowledge about the recorder and were able to play the proposed melodies; they experienced a sense of democratic spirit; and gained insights into the life and works of composers from Pernambuco.
Keywords: recorder; full-time school; meaningful learning